The Impact of Greenhouse Gas Emission Reduction on Economic Growth in the Context of the Green Deal : Analysis in Selected Countries (2020–2022) - Van der Linden, Daniel; Rotschedl, Jiří, 1982-; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
The purpose of this thesis is to investigate the relationship between climate policies and economic growth in five European countries (the Netherlands, Germany, Belgium, France and Denmark) over the period 2015-2022. Utilising a self-developed policy intensity scoring system and employing panel data analysis, the effects of climate measures on emission reduction and economic performance are empirically evaluated. Despite the hypothesis predicating emission reduction on economic costs, the results demonstrate that decoupling is achievable under conditions of policy coherence and timely implementation. The Netherlands and Denmark demonstrate that robust, legally binding measures can result in reduced emissions without compromising economic growth. In parallel, it is demonstrated that the fragmentation of institutions and the presence of structural dependencies in countries such as Germany, Belgium and France serve to limit the effectiveness of climate policies. The regression analysis indicates that policy intensity is not a significant factor in annual emissions changes. However, structural variables such as carbon intensity and gross domestic product (GDP) per capita do demonstrate a significant influence. The application of diagnostic tests has confirmed the presence of heteroskedasticity and cross-sectional dependence, thus emphasising the necessity for robust error corrections. Combining the scoring system with the Kaya identity and LMDI decomposition provides an innovative framework for policy evaluation. This research contributes to the empirical literature on the effectiveness of the European Green Deal and provides policy makers with tools for monitoring and optimising climate policies.
Vedoucí práce: Jiří Rotschedl
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses